Social‐Sportive Work and Local Policy: Reflections From the Flemish Case - Shana Sabbe; Luc De Droogh; Carmen Leenknecht; Annick Verstraete (Social Inclusion, 2025)
Social‐sportive work (SSW) in Flanders operates at the intersection of sport, welfare, and youth work, aiming to enhance accessibility and social inclusion through alternative sporting initiatives. Despite its growing prominence, SSW faces challenges in gaining recognition within local policy structures, which often remain rigid and compartmentalised. This study explores the perspectives of local government officials on the relationship between SSW and local policy. Drawing on a qualitative case study approach, the research was conducted across two Flemish cities between November 2021 and April 2022. The findings support previous research on the tension between the hybrid nature of SSW and the rigid nature of policy structures. Furthermore, the study sheds light on the role of personal affinities, professional backgrounds, and political mandates of local government officials in determining the extent of support for SSW as well as the need for a broader discussion on creating transversal local policy cultures, next to local policy structures.